1997
DOI: 10.20506/rst.16.2.1045
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and control of egg-associated Salmonella enteriditis in the United States of America

Abstract: The isolation rate for Salmonella enterica serotype Enteritidis (SE) in humans in the United States of America (USA) increased from 1,207 sporadic isolates identified in 1976 (0.6 isolates/100,000 population) to 10,201 identified in 1995 (4.0/100,000 population). The proportion of reported Salmonella isolates which were SE increased from 5% to 25% during the same time period. In 1990,1994, and 1995, SE was the most commonly reported Salmonella serotype in the USA. Much of this increase has been associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 22 publications
0
83
0
2
Order By: Relevance
“…Poultry infected with other egg contaminating serotypes, such as Salmonella enterica serovar Pullorum and Salmonella enterica serovar Gallinarum, are associated with drastic weight loss, a sharp decrease in egg production, and increased mortality 80,82 . On the other hand, there are typically no clinical signs in birds infected with S. Enteritidis 44 .…”
Section: Host-parasite Interactions and Clinical Symptoms In Chickensmentioning
confidence: 99%
See 1 more Smart Citation
“…Poultry infected with other egg contaminating serotypes, such as Salmonella enterica serovar Pullorum and Salmonella enterica serovar Gallinarum, are associated with drastic weight loss, a sharp decrease in egg production, and increased mortality 80,82 . On the other hand, there are typically no clinical signs in birds infected with S. Enteritidis 44 .…”
Section: Host-parasite Interactions and Clinical Symptoms In Chickensmentioning
confidence: 99%
“…Although bacteriological screening of hen houses can help to identify flocks at risk 19,42,44 , it is equally difficult to isolate S. Enteritidis from hen houses even if the flock is producing contaminated eggs 14,19,33,41,77 . Previous reports have suggested that S. Enteritidis infection can be decreased in poultry using competitive exclusion by inoculating hatching chicks with beneficial bacterial cultures 65,70 .…”
Section: S Enteritidis Flagellae and Conmentioning
confidence: 99%
“…Investigation of outbreaks and sporadic cases has repeatedly indicated that, when a food vehicle is identified, the most common sources of S. Enteritidis infection are poultry and poultry derivatives, particularly, in the case of outbreaks, undercooked and raw eggs [35,41,65,74]. Although contamination of egg products with other Salmonella serotypes is a long-standing problem, that has been attributed either to the use of damaged eggs or to contamination at or after breaking, the situation with S. Enteritidis is different.…”
Section: Origin Of Human Contaminationsmentioning
confidence: 99%
“…Undercooked and raw eggs have been heavily implicated in human infection with S. Enteritidis (Coyle et al ., 1988;St Louis et al ., 1988;Hogue et al ., 1997;Palmer et al ., 2000;Centers for Disease Control and Prevention, 2004;De Buck et al ., 2004;Crespo et al ., 2005). This serotype is able to cause long-term colonization of the chicken reproductive tract and become deposited within egg contents (Berchieri et al ., 2001;Okamura et al ., 2001;Amy et al ., 2004;Guard-Bouldin et al ., 2004), and in addition will cause external contamination of the shell (Messens et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%